Analisis Iklim Komunikasi Organisasi Dalam Upaya Meningkatkan Kinerja Pengurus - Digna Maoereta, Syifa; Lulus Setiawan, Wawan (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2023)
The purpose of this study was to determine the organizational communication climate in the Margamulya Pangalengan Coffee Producers Cooperative (KPKMP) and to find out how the performance of the management of the Margamulya Pangalengan Coffee Producers Cooperative (KPKMP) was carried out by distributing questionnaires and interviewing members and administrators. The results showed that the Organizational Communication Climate in the Margamulya Pangalengan Coffee Producers Cooperative (KPKMP) was quite good, seen from two aspects of the nature of the organizational climate, namely supportive and defensive. The performance of the management at the Margamulya Pangalengan Coffee Producers Cooperative (KPKMP) is still quite good, which is caused by several factors such as the number of jobs, quality of work, level of punctuality, attendance and ability to cooperate.